2010
DOI: 10.1002/ejsp.777
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of perpetrators and victims of peer victimization: An extended crossed-categorization approach

Abstract: This research uses a crossed-categorization design for examining the perception of peer victimization. Using vignettes and an experimental design, perpetrator and victim evaluations of Dutch and Turkish-Dutch early adolescents were examined in terms of ethnic and gender similarities between (1) respondent and perpetrator, (2) respondent and victim, and (3) perpetrator and victim. When the perpetrator was a double-ingroup member of the respondent (same ethnicity and same gender), perpetrators were evaluated les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
1
8
1
1
Order By: Relevance
“…However, there are two reasons to assume that the role of cross‐categorization was limited. First, research among children (using ethnicity and gender as two characteristics) has not found clear evidence for crossed‐categorization effects in which sharing one characteristic leads to more positive evaluations than sharing none of the two characteristics (Verkuyten, Weesie, & Eijberts, ). Second, the effects of the acculturation strategies on participants’ liking of out‐group and in‐group peers were unrelated to gender.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are two reasons to assume that the role of cross‐categorization was limited. First, research among children (using ethnicity and gender as two characteristics) has not found clear evidence for crossed‐categorization effects in which sharing one characteristic leads to more positive evaluations than sharing none of the two characteristics (Verkuyten, Weesie, & Eijberts, ). Second, the effects of the acculturation strategies on participants’ liking of out‐group and in‐group peers were unrelated to gender.…”
Section: Discussionmentioning
confidence: 99%
“…This means, for instance, that children who received the first version of the questionnaire only rated the following four combinations: a Turkish boy not helping another Turkish boy, a Dutch boy not helping another Dutch boy, a Turkish girl not helping another Turkish girl, and a Dutch girl not helping another Dutch girl. Also following previous research (Verkuyten et al., ), the ethnic group membership of helper and recipient were systematically varied by using four different Turkish and Dutch first names, thereby generating four possible combinations. The Turkish first names for boys were Ömer, Murat, Ahmet, Mehmet, and for girls Fatma, Leyla, Nuray, and Derya.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous research, an incomplete random block design was used with 16 versions (e.g., Verkuyten, Weesie, & Eijberts, 2010). Because of demand load, each responding child was presented with a different combination of ethnicities for the four stories.…”
Section: Studymentioning
confidence: 99%
“…Such comparisons have not been regularly made in the literature. A notable exception is a study by Verkuyten, Weesie, and Eijberts (2011) that used a cross-categorization design to examine how children evaluated hypothetical perpetrators and victims of exclusion. The authors found that children's judgments depended on the match between the combination of their own ethnicity and gender and the ethnicity-gender combination of the protagonists.…”
Section: Introductionmentioning
confidence: 99%